2020
DOI: 10.3390/biom10111518
|View full text |Cite
|
Sign up to set email alerts
|

Fragment Library of Natural Products and Compound Databases for Drug Discovery

Abstract: Natural products and semi-synthetic compounds continue to be a significant source of drug candidates for a broad range of diseases, including coronavirus disease 2019 (COVID-19), which is causing the current pandemic. Besides being attractive sources of bioactive compounds for further development or optimization, natural products are excellent substrates of unique substructures for fragment-based drug discovery. To this end, fragment libraries should be incorporated into automated drug design pipelines. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 30 publications
2
30
1
1
Order By: Relevance
“…With this ultimate goal in mind, we first assembled the most complete up-to-date COlleCtion of Open Natural ProdUcTs (COCONUT) that we have been continuously curating and annotating. Studies [ 10 , 11 ] showed that fragments from NPs present in COCONUT have high diversity and structural complexity, which makes it, among other possible applications, a suitable source for drug discovery and can be included in drug design pipelines. Our next step was to make this data available to the scientific community as a full-fledged online natural products database, maintained at https://coconut.naturalproducts.net .…”
Section: Introductionmentioning
confidence: 99%
“…With this ultimate goal in mind, we first assembled the most complete up-to-date COlleCtion of Open Natural ProdUcTs (COCONUT) that we have been continuously curating and annotating. Studies [ 10 , 11 ] showed that fragments from NPs present in COCONUT have high diversity and structural complexity, which makes it, among other possible applications, a suitable source for drug discovery and can be included in drug design pipelines. Our next step was to make this data available to the scientific community as a full-fledged online natural products database, maintained at https://coconut.naturalproducts.net .…”
Section: Introductionmentioning
confidence: 99%
“…Some molecular fingerprints, such as SMILES fingerprint (SMIfp) (Schwartz et al, 2013 ), and structural interaction fingerprint (SIFt) (Deng et al, 2004 ), evaluate structural features related to intermolecular interactions, such as hydrophobic contacts, polar interactions, and hydrogen bond acceptors and donors (interaction fingerprints) (Desaphy et al, 2013 ). Considering that natural products are chemically complex and structurally different from the synthetic libraries, the analyses of their structures using molecular fingerprints can provide insights, evidencing some structural similarities (see example in Figure 2B ) (Gu et al, 2013 ; Tao et al, 2015 ; Floros et al, 2016 ; Galúcio et al, 2019 ; Chávez-Hernández et al, 2020 ).…”
Section: Computational Methods Applied In Virtual Screening Approachesmentioning
confidence: 99%
“…Crystallography of HCoV enzymes and reports on their potential ligands, have assisted computational methods (docking-scoring calculations of protein-ligand interactions using similarity to known actives) to discover SARS-CoV-2 inhibitors [ 27 ]. Virtual screening is extensively employed for the moment, to identify potential ligands from SMs and in-house NPs libraries [ 130 , 131 , 132 ].…”
Section: Nps With Anti-hcov Potentialmentioning
confidence: 99%